Integrating Information into Electronic Health Records. - Wong, Carol. (2017)
Abstract: Widespread adoption of health information technologies holds the potential of transforming the way healthcare is delivered by improving quality, enhancing safety, reducing workload and reducing cost. The increased availability of patient information and decision support at the point of care has tremendous potential for reducing errors and increasing coordinated care. The goal of this research was to understand the methods of information transfer between emergency medical services and hospital emergency rooms. A design of an electronic patient chart representing the ideal of seamlessly transferred data was created and compared with a design reflecting the interoperability issues that are common. A usability test was run to rate heuristics of the design. Results indicate that integrating data supports decision making and reduces the reliance on memory making electronic health records more effective.; Thesis (M.S.)--Tufts University, 2012.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Dan Hannon.; Committee: Dan Hannon, Anil Saigal, and Harry Selker.; Keywords: Information technology, and Health care management.